Evaluasi Pengelolaan Dana Bantuan Operasional Sekolah di SD Negeri 027 Tarakan Kaswandi - Kaswandi . (Universitas Muhammadiyah Malang, 2015)
Evaluasi Pengelolaan Dana Bantuan Operasional Sekolahdi SD Negeri 027 TarakanKaswandiPengawas Dinas Pendidikan TarakanEmail: kaswanditrkn@gmail.comAbstract:The research objective was to describe about planning, implementation and supervision, evaluation and reporting and responsibility of funding management of school operational board at public elementary school 027 Tarakan. The results showed that the arrangement of the planning of school funding and activity was on time in the beginning of the estimation year, based on priority scale of school need, and involve school committee and teachers. The implementation had not been success overall because the distribution of BOS funding was still late. Bookkeeping administration had been relevant to the regulation of national education minister No. 51 year 2011. The supervision aspect had not succeeded yet because there was not supervision from school committee and local department of education periodically. The evaluation activity by committee had been implemented though it was not maximum. The report of BOS funding management at public elementary school 027 can be stated as success because it has made the report based on technical guide of BOS funding management in line with the regulation of National Education Minister No. 51 year 2011Keywords: evaluation, management, assistance, operations, school.Abstrak:Penelitian ini bertujuan untuk mendeskripsikan tentang perencanaan, pelaksanaan, pengawasan, evaluasi serta pelaporan dan pertanggungjawaban pengelolaan dana BOS di SDN 027 Tarakan. Hasil penelitian menunjukkan bahwa penyusunan RKAS tepat waktu diawal tahun anggaran, berdasarkan skala prioritas kebutuhan sekolah, serta melibatkan komite dan guru. Aspek pelaksanaan belum seluruhnya berhasil dikarenakan penyaluran dana BOS masih terlambat. administrasi pembukuan sudah sesuai dengan Permendiknas No. 51 Tahun 2011. Aspek pengawasan masih belum berhasil karena belum ada pengawasan dari pihak komite sekolah dan dinas terkait secara berkala. Aktifitas evaluasi oleh pihak komite sudah dilakukan meskipun belum maksimal. Pelaporan pengelolaan dana BOS di SDN 027 dapat dikatakan sudah berhasil dikarenakan sudah membuat laporan sesuai dengan petunjuk teknis pengelolaan dana BOS sesuai dengan Permendiknas No. 51 Tahun 2011.Kata kunci: evaluasi, pengelolaan, bantuan, operasional, sekolah.